KESENIAN GONDANG GONG PADA MASYARAKAT KELURAHAN KOTALAMA KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Wildani, Hasbina; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The Village Kotalama have art that still survive, namely Art gondang gong identical to traditional art used on special occasions and religious customs. But the times make the traditional arts is nearly extinct and is rarely played by young children. Concerned with the state of traditional art gondang gondang gong gong player as black to form a group of traditional art gondang gong named Sendayuang Kunto. Issues raised in this study are 1. How does the function and role of art gondang gong culture in the community in the village Kotalama, 2. Factors inhibiting the development of the arts in the Village Kotalama gondang gong Kunto Darussalam District of Rokan Hulu.The method used was a qualitative research method. Research location in the Village District of Kunto Darussalam Kotalama Rokan Hulu. That is the subject of this research is gondang player gong consisting of five people and one person who is a substitute that will replace one of the players remain if the other players can not come or other obstacles, two public figures such as Mamak tribe, 3 residents who have done custom events such as weddings. Data collection techniques used were interviews and documentation.Results of research conducted in general the writer can say that the awareness of young people now to preserve the arts gondang gong is very minimal, it is proved by seeing the age of the players gondang gong mean age Â± 55 years and over, and one of them is a grandmother whose age is now 77 years old.Keywords: Art, Gondang Gong, Traditional.